Dental Trauma: A Painful Experience for the Paediatric Population From a Pediatric Dentist’s Point of view - Datta, Arpita; Mohanty, Susant (Journal of Biomedical and Pharmaceutical Research, 2023)
A child’s general health is ensured by various sorts of physical activities but none of these activities should cause any difficulties or either hampers their growth and development. The most important aspect to these being the wellbeing of oral health of kids from sudden injuries which most of the times is overlooked by both the parents, caretakers or pediatricians’. Trauma may massively impact the psychological health of the adolescents as well. There comes the role of an Oro-Dental Specialist, who can draw a margin between the distress and difficulties faced by the pediatric patients due to such fatalities and also spread awareness among the parents. Preventive therapeutic steps help to depicture the current scenario and help provide a better life for future generations. Keywords: Traumatic Dental Injuries, Anterior teeth, Oral Health, Complications.